Practices Regarding Iron Supplements and Iron Rich Foods among Adolescent Girls at Islamic Senior High School - Meikawati, Wulandari; Handoyo, Wahyu; Astuti, Rahayu; Nurullita, Ulfa; Aminah, Siti (Diversity: Disease Preventive of Research Integrity, 2023)
The primary nutritional concern among adolescent girls is iron-deficiency anemia, which requires prompt attention to prevent complications during pregnancy. One of the strategies for prevention involves the consumption of iron supplements (IS) and high-iron foods. This study aims to delineate the menstrual history, eating patterns, and practice associated with consuming IS and high-iron foods. Employing a descriptive approach, the research was conducted at Islamic Senior High School (MAN 2) Kudus. The sample, comprising 184 individuals, was selected through purposive sampling. The research employed a questionnaire and a Food Frequency Questionnaire (FFQ) as instruments. The findings indicate that only 19.6% of the respondents reported having IS always available at home. The majority (62.0%) had consumed IS at some point. However, only 8.1% consumed IS regularly during menstruation, and 4.3% consumed it regularly when not menstruating. The majority of respondents frequently consumed high-iron foods (1-5 times per week), including chicken/duck (84.8%), eggs (80.4%), fish (76.7%), and meat (60.9%). It is hoped that schools and local healthcare services can enhance educational efforts regarding the benefits of IS consumption for adolescent girls. The practice of consuming IS and high-iron foods from halal sources are a part of maintaining bodily health and constitutes an obligation for every Muslim.